2019
DOI: 10.1016/j.ejim.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker assessment for early infarct size estimation in ST-elevation myocardial infarction

Abstract: Background: High-sensitivity cardiac troponin T (hs-cTnT) represents the biomarker of choice for infarct size (IS) estimation in patients with acute ST-elevation myocardial infarction (STEMI). However, admission values of hs-cTnT are only weakly associated with IS. The aim of this study was to investigate the incremental value of different biomarkers measured on admission for IS estimation in STEMI patients. Methods: In this prospective observational study, we included 161 consecutive STEMI patients treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Meanwhile, time-concentration curves and their changes for the plasma levels of total CK, CK-MB from time of enrollment to 110 h have been displayed (Fig. 4A,B), which was commonly used in evaluating the degree of myocardial necrosis in clinical practice and associated with adverse clinical outcomes 1315 . The curves for CK, CK-MB reached peak levels by 6 to 12 h, and decreased steadily thereafter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, time-concentration curves and their changes for the plasma levels of total CK, CK-MB from time of enrollment to 110 h have been displayed (Fig. 4A,B), which was commonly used in evaluating the degree of myocardial necrosis in clinical practice and associated with adverse clinical outcomes 1315 . The curves for CK, CK-MB reached peak levels by 6 to 12 h, and decreased steadily thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…In a multivariate regression model, coronary dsDNA remained an independent correlation with in-hospital MACEs. In addition, we explored the association between the change of CK-MB and AUC CK-MB, which commonly used in evaluating the degree of myocardial necrosis in clinical practice and associated with adverse clinical outcomes 1315 , and NETs (dsDNA, MPO/DNA). Although, there was no correction been found, coronary dsDNA was more sensitive than other conventional prognostic markers, such as troponin T and CK-MB.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in hs-cTnT following exercise in the present meta-analysis was similar in pattern to that of early release kinetics observed in a clinical setting (Thygesen et al, 2018), but the peak concentration was much lower (33 ng.L −1 ) and the recovery was earlier in our meta-analysis compared with clinical conditions. As a quantitative marker of cardiomyocyte injury, the more pronounced the change of hs-cTnT, the higher the likelihood of cardiac injury (Marjot et al, 2017;Tiller et al, 2019). Concentrations lower than 50 ng L −1 were considered to represent micro myocardial infarction, chronic heart disease, or non-myocardial infarction conditions, such as kidney disease (Kozinski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be considered a predictive biomarker for all-cause and cause-specific mortality [ 60 ]. According to Tiller et al, in patients with STEMI undergoing primary PCI, the levels of NT-proBNP at admission were increased in those with an infarct size greater than 19% of the LV myocardium as evaluated by cardiac magnetic resonance imaging in comparison with those with a smaller affected area (140 ng/L vs. 86 ng/L, p = 0.008), an early assessment of the amount of the cardiac damage being an essential instrument for post-STEMI risk stratification [ 61 ]. Celebi et al [ 62 ] showed that a single determination of NT-proBNP levels being greater than 400 pg/dL within 12 h offers a predictive value for LV aneurysm (LVA) development.…”
Section: Resultsmentioning
confidence: 99%